(untitled) (Dhaka University Journal of Biological Sciences, 2025)
The present study was undertaken to evaluate the amount and extent of heavy metals contamination in the vegetable crops, rice and grasses grown at different industrial sites in and around Dhaka. In most of the studied crops, Zn and Cu concentrations were found above the phytotoxic limit, while Ni, Pb and Cd contents were found below the phytotoxic limit but above the tolerable range for human consumption. Among the crops, Kalmisak (Ipomoea aquatica) was the highest accumulator of Pb and Cd, whereas grass was found the highest accumulator of Cu and Ni. The highest accumulation of Zn was found in Lalsak (Amaranthus cruentus), followed by Kalmisak. The transfer factors varied considerably among crops and also within different metals. Among the industries, tube and steel mills as well as battery industries might be responsible for contributing higher levels of heavy metals in soils and plants of these areas. Dhaka Univ. J. Biol. Sci. 34(2): 41-56, 2025 (July)